PEMBENTUKAN WIRAUSAHA BARU BUSANA KE ARAH PENGEMBANGAN KEHIDUPAN INDUSTRI BUSANA - Hartatianti, - (Jurusan Teknologi Jasa dan Produksi, Fakultas Teknik, Universitas Negeri Semarang, 2008)
Graduate of Education Fashion Study Program do not have to become teacher,but also have to create the opportunity of occupation for their own and others, throughentrepreneurship. This activity represent devotion to society, developing new small scaleclothing business to be instructed to become bigger industry. It needed partnership with